Multiyear phytoremediation and dynamic of foliar metal(loid)s concentration during application of Miscanthus × giganteus Greef et Deu to polluted soil from Bakar, Croatia - Pidlisnyuk, Valentina; Shapoval, Pavlo; Zgorelec, Željka; Stefanovska, Tatyana; Zhukov, Oleksandr (Environmental science and pollution research international, 2020)
The multiyear cultivation of Miscanthus × giganteus Greef et Deu (M.×giganteus) at the soils polluted by metal(loid)s were researched. The biomass parameters and concentrations of elements: Ti, Mn, Fe, Cu, Zn, As, Sr, and Mo were determined in the plant's organs at harvest. The same metal(loid)s were monitored in the plant's leaves throughout three vegetation seasons. The principal component analysis and general linear model approaches were applied for statistical evaluation followed by Box-Cox transformation. The difference in the distribution of elements in the plant, the content of elements in the soil, various regime of uptake to the plant tissues, and the year of vegetation were analyzed as driving factors of the phytoremediation. The results showed that the leading promoter was the factor of the zone, which was the most essential for Ti, Fe, and Cu and the smallest for Mn. The factor of differences in soil pollution was essential for Zn and Mo, much less for As, Sr, and Mn, limited for Fe, and was not seen for Ti and Cu. The factor of the interrelation effects of the zone and experiment reflected the different regime of uptake for the plant tissues was seen for two elements: more prominent for Cu and smaller for Ti. While analyzing the dynamic of foliar concentrations of the metal(loid)s during 3 years, two groups were defined. Firstly, Fe, Ni, Mn, and Sr showed stable curves with limited distribution of the plant life cycle. Secondly, As, Zn, Cu, and Mo showed different fluctuations in the curves, which can be attributed to essential influence of those elements to the plant life cycle. Further research will be focused on the application of M.×giganteus to the polluted soil in a bigger scale and comparison results of laboratory and field experiments.
Keywords: Dynamic of foliar concentration; Biodegradation, Environmental; biodegradace; Soil Pollutants; Miscanthus × giganteus; Rijeka-Bakar area; Metals, Heavy; látky znečišťující půdu; Metal(loid)s polluted soil; Soil; Chorvatsko; Croatia; Phytoremediation; půda; těžké kovy